Investigation of Asphalt Mixture Containing Crystalline Waterproofing Agent (CWA) For Moisture Damage Resistance - Md Hanif, Shahriz Amri; Buhari, Rosnawati (Recent Trends in Civil Engineering and Built Environment, 2022)
Moisture damage is one of the common problems in road pavement. These failures are mostly due to stripping of aggregate and asphalt when making contact with moisture in any kind of ways. Loss of adhesion bond between aggregate and asphalt due to stripping cause the road pavement to lower it durability and performance making it is more likely to fail. In order to enhance the performance of asphalt mixture, a modification towards the asphalt mixture where various mineral filler used to the asphalt mixture. In this study, Crystalline Waterproofing Agent (CWA) was used as a filler to evaluate the effectiveness of the filler in resist moisture damage when water penetrate or infiltrate into the asphalt mixture. The aim is to determine the optimum CWA content to resist the moisture damage that may arise to asphalt mixture from previous studies. The tests result that have been obtained including aggregate gradation, penetration test, softening test, Indirect Tensile Test and Static Immerse Test. ITS test shows several TSR data that used different percentages of CWA. Results shows that higher content of CWA in asphalt mixture resulted in higher value of TSR. In static immerse test, 4 different percentage of CWA used in asphalt mixture was analyse to evaluate the effectiveness of CWA in resist moisture damage. Results show the stripping between aggregate and asphalt are reduced as content of CWA increase. To conclude, the use of CWA in mix design affected the performance of asphalt mixture. It basically increased the resistance towards moisture damage.